2012
DOI: 10.1021/es3029389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combined Diesel Particle Filter-DeNOx System (DPN) on Reactive Nitrogen Compounds Emissions: A Parameter Study

Abstract: The impact of a combined diesel particle filter-deNO(x) system (DPN) on emissions of reactive nitrogen compounds (RNCs) was studied varying the urea feed factor (α), temperature, and residence time, which are key parameters of the deNO(x) process. The DPN consisted of a platinum-coated cordierite filter and a vanadia-based deNO(x) catalyst supporting selective catalytic reduction (SCR) chemistry. Ammonia (NH₃) is produced in situ from thermolysis of urea and hydrolysis of isocyanic acid (HNCO). HNCO and NH₃ ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 48 publications
8
37
2
Order By: Relevance
“…This allowed the SCRequipped diesel engine to meet and exceed the most recent EPA Tier 4 emission standard of ∼ 1.6 g of NO x kg fuel −1 (or 0.4 g of NO x kW h −1 ). Similar to earlier work (Wentzell et al, 2013;Heeb et al, 2012Heeb et al, , 2011Suarez-Bertoa and Astorga, 2016), we observed HNCO when no NH 3 was injected, implying that the HNCO was produced either in the engine cylinder or in the aftertreatment devices upstream of the SCR (DOC + DPF). For six of the seven experiments performed with diesel fuel, HNCO emissions were reduced by 5-40 % with increasing NH 3 injections.…”
Section: No X and Hnco Emission Factorssupporting
confidence: 90%
See 4 more Smart Citations
“…This allowed the SCRequipped diesel engine to meet and exceed the most recent EPA Tier 4 emission standard of ∼ 1.6 g of NO x kg fuel −1 (or 0.4 g of NO x kW h −1 ). Similar to earlier work (Wentzell et al, 2013;Heeb et al, 2012Heeb et al, , 2011Suarez-Bertoa and Astorga, 2016), we observed HNCO when no NH 3 was injected, implying that the HNCO was produced either in the engine cylinder or in the aftertreatment devices upstream of the SCR (DOC + DPF). For six of the seven experiments performed with diesel fuel, HNCO emissions were reduced by 5-40 % with increasing NH 3 injections.…”
Section: No X and Hnco Emission Factorssupporting
confidence: 90%
“…Fourth, the emission factors for HNCO from this study (31-56 mg kg fuel −1 ) compared reasonably well with those from an SCR-equipped diesel engine tested by Heeb and coworkers (Heeb et al, 2011(Heeb et al, , 2012) (29-32 mg kg fuel −1 ) but were slightly higher than the two SCR-equipped diesel vehicles tested by Suarez-Bertoa and Astorga (2016) (1.3-9.7 mg kg fuel −1 ). However, in sharp contrast to our findings from Fig.…”
Section: Comparison With Earlier Worksupporting
confidence: 78%
See 3 more Smart Citations